KOMUNIKASI PEMBELAJARAN VIRTUAL DALAM SPIRIT MISERICORDIAE VULTUS - Norbertus Jegalus (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
This article analyzes the problem of virtual learning communication that does not answer the demands of humanist education, namely carrying out not only "transfer of knowledge" and "transfer of skills" but also "transfer of values". What is difficult to do in virtual lectures is not the transfer of knowledge and skills but the transfer of values. Because knowledge can be learned and skills can be trained through technology, but values ​​are not primarily learned or trained using tools but are put into practice and it is not the case in virtual lectures. The weakness of virtual lectures is that there is no face-to-face meeting, even though such an encounter is demanded by all theories of humanist education. Face-to-face communication is important in education, because this type of communication is needed to create the spiritual and emotional intelligence of students. Meanwhile virtual lectures only answer intellectual intelligence. Facing this condition, lecturers are required to have a caring spirit as taught by Bulla "Miserdicodiae Vultus". Caring is the basic value for other humanist values ​​that must be possessed by a lecturer, such as: dedication, patience, responsibility and attention.